[PP.29.34] LOWER BLOOD PRESSURE IS RELATED TO WORSE FUNCTIONAL OUTCOME AFTER STROKE IN THE ELDERLY. (September 2017) - Alonzo, C.; Brescacín, L.; Zurrú, M.; Linares, G.; Fucile, G.; Pigretti, S.; Cámera, L.; Waisman, G.
Abstract : Objective: Optimal blood pressure target after a stroke in the very elderly (> 80 years) is still a matter of debate, mainly because there are concerns regarding possible deleterious effects of low blood pressure on brain microcirculation. We aim to evaluate the relationship between one-month after stroke blood pressure and functional outcomes, and if differences could be related to age. Design and method: Acute ischemic stroke patients were prospectively included in a multidisciplinary secondary stroke prevention program. Demographic data and pre-stroke vascular risk factor profile and control were obtained from electronic medical records. For the purpose of the analysis, stroke outcomes (cognition by MMSE and functional status by Barthel index and m-Rankin scale) were analyzed according to 30-day SBP and DBP in older and younger than 80 years. Results: 562 (42%) of 1476 stroke patients included between December 2006 and December 2015 were older than 80 years. These patients had higher prevalence of hypertension (85% vs 79%, p 0.004), dyslipidemia (74% vs 64%, p 0.0001), diabetes (17% vs 12%, p 0.007), atrial fibrillation (28% vs 5%, p 0.001), chronic kidney disease (41% vs 29%, p 0.0001), were more likely to be female (58% vs 50%, p 0.003). Blood pressure levels and one-month stroke outcomes in patients older and younger than 80 years are shown in the table. Figure. No caption available. Conclusions: Disability and poor cognitive and functional outcomes were related with lower blood pressure levels after stroke in elderly patients. Vascular aging may increase brain vulnerability to hypoperfusion by reducing the ability to adapt blood flow delivery to energy demands, leading to worse outcomes in elderly patients.